Iron‐Catalyzed Hydroboration: Unlocking Reactivity through Ligand Modulation. Issue 33 (6th July 2016) - Espinal‐Viguri, Maialen; Woof, Callum R.; Webster, Ruth L.
Abstract: Iron‐catalyzed hydroboration (HB) of alkenes and alkynes is reported. A simple change in ligand structure leads to an extensive change in catalyst activity. Reactions proceed efficiently over a wide range of challenging substrates including activated, unactivated and sterically encumbered motifs. Conditions are mild and do not require the use of reducing agents or other additives. Large excesses of borating reagent are not required, allowing control of chemo‐ and regioselectivity in the presence of multiple double bonds. Mechanistic insight reveals that the reaction is likely to proceed via a highly reactive iron hydride intermediate. Abstract : Iron nails it : Iron(II) hydroboration (HB) of alkenes and alkynes has been developed. Substrates include renewable sources and a change in ligand shows a vast change in regioselectivity. Alkynes have been functionalized, and a unique example of double hydroboration to give the 1, 1‐dipinacolborane product is provided (see scheme).